GROUND SURFACE TEMPERATURE HISTORIES INFERRED FROM DEEP BOREHOLE TEMPERATURE-DEPTH DATA IN EASTERN SIBERIA - Dorofeeva R.P.; Shapova M.V.; Shen P.Y. (My University, 2002)
Temperature–depth data from 14 deep boreholes, located in the Irkutsk amphitheater and Baikal rift zone in Eastern Siberia, have been used to infer ground surface temperature (GST) histories for the last 100 ka. The results show that the estimated small-scale and recent GST changes and the long-term mean have been significantly contaminated by the presence of drilling disturbances. On the other hand, large-scale features, such as the Pleistocene/Holocene (P/H) transition, appear to have been adversely affected to a much lesser extent, as suggested by the internal consistency of the inverse results. The estimated GST histories exhibit a pattern of north to south variation, with the P/H warming varying from about 25 K at a latitude of 56°N to less than 8 K at 54°N and then back to 25 K at 52°N. The timing and duration of the transition also vary. In the north, warming began as early as 90 ka and reached a maximum at about 7 ka, and in the south, warming did not begin until about 20 ka and reached a maximum at about 4 ka.